L. plantarum UBLP-40 Versus the Combined Formula of L. rhamnosus UBLP-58 and B. longum UBBL-64 in Excisional Wound Healing: A Cellular Perspective - Moysis Moysidis; Angeliki Chorti; Angeliki Cheva; Ioanna Abba Deka; Georgios Tzikos; Christoforos Kosmidis; Ioannis Koutelidakis; Joulia K. Tsetis; Theodossis Papavramidis; Katerina Kotzampassi (Pharmaceuticals)
Introduction: The utilization of probiotics in enhancing the active healing of skin wounds represents a burgeoning trend in contemporary medicine. Previous research has extensively explored wound healing mechanisms involving the strains of Lactiplantibacillus plantarum, Lacticaseibacillus rhamnosus, and Bifidobacterium longum. This study seeks to compare and interpret cellular findings derived from immunohistochemical and pathological applications. Methods: Three groups (the control, Lactiplantibacillus plantarum (RO1) group, and Lacticaseibacillus rhamnosus and Bifidobacterium longum (PRO2) group) underwent histological analysis, and microscopic cell counting were employed, offering insights into dynamic changes among neutrophils, lymphocytes, plasmacytes, mast cells, fibroblasts, and newly formed vessels across distinct treatment groups and temporal intervals. Results: The neutrophil count was found to be elevated in PRO2 on day 2, while the same group resulted in the highest decline on day 15. The number of fibroblasts peaked on day 4 for the PRO1 group, compared to the other two groups, which peaked on day 8. The lymphocyte count was the highest in the control group, while they peaked on day 4 in PRO2. The mast cells and plasmacytes were variable and sparse among all groups and time frames. Neovascularization was promoted by PRO1 and PRO2 groups on day 4 and remained high on day 8 for PRO2. Conclusions: Probiotic strains can be beneficial to the human population and in assisting skin wound healing, each strain working differently and more effectively in different healing phases. Thus, a combined formula containing different probiotics to modulate various healing phases is desirable.